2021
DOI: 10.33594/000000470
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Host Interactions of Enteroviruses and Parvovirus B19 in Myocarditis

Abstract: Viral diseases are a major threat to modern society and the global health system. It is therefore of utter relevance to understand the way viruses affect the host as a basis to find new treatment solutions. The understanding of viral myocarditis (VMC) is incomplete and effective treatment options are lacking. This review will discuss the mechanism, effects, and treatment options of the most frequent myocarditis-causing viruses namely enteroviruses such as Coxsackievirus B3 (CVB3) and Parvovirus B19 (PVB19) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 191 publications
0
9
0
Order By: Relevance
“…It has previously been demonstrated that airway inflammation is exacerbated and the cell cycle blocked after influenza virus infection ( 37 , 44 ), and a previous study reported that cell cycle arrest promoted viral replication to increase inflammation ( 44 ). The present study elucidated the role of RKIP in promoting recovery of the cell cycle after its arrest to alleviate the inflammatory responses induced by IAV in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that airway inflammation is exacerbated and the cell cycle blocked after influenza virus infection ( 37 , 44 ), and a previous study reported that cell cycle arrest promoted viral replication to increase inflammation ( 44 ). The present study elucidated the role of RKIP in promoting recovery of the cell cycle after its arrest to alleviate the inflammatory responses induced by IAV in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that autophagosomes are involved in the regulation of many important physiological processes, changes in autophagosome levels may also influence the development of viral myocarditis. Recent studies have shown that autophagy may influence the development of myocarditis by inhibiting viral replication, influencing cell apoptosis and inducing cellular immune responses ( Luo et al, 2010 ; Yoshida, 2017 ; Ho et al, 2021 ).…”
Section: Autophagy In Viral Myocarditismentioning
confidence: 99%
“…The local immune environment in cardiac tissues in viral myocarditis profoundly affects the progression of viral myocarditis, which can be divided into three main phases. The first phase is viral entry and innate immune system activation, the second phase is adaptive immune response activation, and the third phase is recovery or disease progression ( Ho et al, 2021 ).…”
Section: Autophagy In Viral Myocarditismentioning
confidence: 99%
See 2 more Smart Citations